2020
DOI: 10.18632/aging.202192
|View full text |Cite
|
Sign up to set email alerts
|

Screening and functional prediction of differentially expressed circular RNAs in human glioma of different grades

Abstract: Circular RNAs (circRNAs) have a critical regulatory function in human glioma. However, novel circRNAs related to different pathological grades of glioma and their crucial potential function are worth screening and prediction. CircRNA expression profiling was performed for 6 paired high- and low-grade glioma tissues and 5 adjacent normal brain tissues through next-generation sequencing. Quantitative real-time PCR (qRT-PCR) was conducted to validate circRNA expression. Bioinformatics analysis was performed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Furthermore, the low level of circKCNN2 was significantly associated with unfavorable OS and RFS of HCC. circKCNN2 was previously reported to be associated with the development of glioma 22 . These data, together with our results, indicate that circKCNN2 may function as a tumor suppressor in multiple cancer types.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the low level of circKCNN2 was significantly associated with unfavorable OS and RFS of HCC. circKCNN2 was previously reported to be associated with the development of glioma 22 . These data, together with our results, indicate that circKCNN2 may function as a tumor suppressor in multiple cancer types.…”
Section: Discussionsupporting
confidence: 88%
“…Fifteen potentially functional circRNAs that had at least one significantly enriched gene set were selected from the 53 circRNA candidates (Figure 1A, right). Among the 15 circRNAs, circKCNN2 (also known as hsa_circ_0127664) was previously reported to be significantly downregulated in brain tissue of patients with progressive glioma, suggesting it may be a tumor suppressor 22 . Therefore, circKCNN2 was selected for further investigation as a potential suppressor for HCC recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested that epigenetic modification plays a crucial role in the pathogenesis of GBM. 20,21 Recently, N6methyladenosine modification has attracted extensive attention, but the specific mechanism of this novel RNA modification in the occurrence and development of GBM has not been fully studied, especially in circRNA. 11 We used RNA N6-methyladenosine sequencing to explore the state of N6-methyladenosine-circRNA modifications in GBM tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma presents a challenging clinical situation that causes notable mortality and morbidity [1]. circRNAs make a signi cant contribution to the regulation of cell cycle, angiogenesis, metastasis, and drug resistance of glioma cells [33]. This study elucidated that METTL3-mediated circDCL1 promoted CTNNBIP1 transcription by sponging miR-671-5p, thus repressing the malignant proliferation of glioma cells (Fig.…”
Section: Discussionmentioning
confidence: 90%